The modelling of spatial units (parcels) in the land administration domain model (LADM) - Lemmen, Christiaan (2012)
The Land Administration Domain Model (LADM) is under development within the Technical Committee 211 (TC211) of the International Organisation for Standardization (ISO) and identified as ISO 19152. Within the LADM classical cadastral concepts as “parcel” and “boundary” have been extended to be able to include spatial representations of overlapping tenures or claims and also multidimensional objects (3D and 2D/3D, combined with temporal dimensions). Furthermore, a series of new representations are possible apart from topologically well structured parcels (here called spatial units). Text based, sketch based, point based, line-based, polygon based, or topological based representations of spatial units are possible. The topological spatial units are defined by a consistent topological structure(with no gaps, overlaps or intersections), which is in contrast with a set of polygons, where a consistent topological structure is not guaranteed. A line-based spatial unit is represented by a collection of lines which may be collected from different sources or surveys. A point-based spatial unit contains only the coordinates of the unit’s reference point. A text based spatial unit is not represented by coordinates, but has a spatial unit description in words, e.g. the metes and bounds system (a spatial unit description in terms of distance, direction, and landmarks). All these spatial units may have a 3D representation, and a provision is made for a mixture of 2D and 3D spatial units to co-exist. A level is a collection of spatial units with a geometric or thematic coherence. The concept of level is related to the notion of “legal independence” from ‘Cadastre 2014’. This allows for the flexible introduction of spatial data from different sources and accuracies, including utility networks, buildings and other 3D spatial units, such as mining claims, or construction works. The paper explores the LADM spatial component, which is further based on ISO standards, combined with new concepts as “boundary face string” and partially unbounded primitives. Spatial profiles and the different spatial representations are used to demonstrate the flexibility of spatial representations of this domain model; for formal and non formal land administrations systems alike. The first trial implementation of the Queensland (Australia)Digital Cadastral Database (DCDB) for 2D parcel encoding using the line-based spatial profile will be discussed in detail, together with the polygon based spatial profile for the spatial units of the Portuguese land administration.